A comparative study on cardiovascular disease risk factors in Korean adults according to clinical depression status. (May 2018) - Seo, Yuri; Je, Youjin
Abstract: This study was conducted to compare the association between depression and cardiovascular disease risk factors among Korean adults. This study was based on the data from the Korea National Health and Nutrition Examination Survey conducted in 2012–2014. Using a multivariable logistic regression model, we calculated odds ratios (ORs) and 95% confidence intervals (CIs). A total of 10, 359 subjects aged 19–64 years were selected, and 432 subjects (74 men, 358 women) were included in the physician-diagnosed depression group. Several cardiovascular risk factors were associated with higher odds of clinical depression. For men, high waist circumference (≥91.3 cm) and body mass index (≥25.0 kg/m 2 ) were significantly associated with increased odds of depression, and high physical activity (≥50 MET h/week) was associated with decreased odds of depression. Men with dyslipidemia and metabolic syndrome had 2.43-fold and 2.0-fold higher odds of depression than those without the diseases. For women, current smokers had 2.25-fold higher odds of depression than nonsmokers, and frequent alcohol drinkers (≥4 times/week) also had 2.88-fold higher odds of depression than nondrinkers. Korean adults with clinical depression had a higher prevalence of some risk factors for cardiovascular diseases than those without depression. Highlights: There have been several studies on cardiovascular disease risk factors in relation to depression status. However, there are limited data on the association between depression and cardiovascular disease risk factors in Korean adults, especially for men. We investigated whether lifestyle factors, anthropometric and clinical measurements leading to cardiovascular disease were associated with the prevalence of depression in Korean adults, using a large nationally representative sample of Korean population, and confirmed that there are positive associations between depression and several cardiovascular disease risk factors among Korean adults. Our findings support early detection and management of depression among people with or at high risk of cardiovascular disease. Given the increasing importance of depression in many countries, the cardiovascular disease risk factors should be carefully monitored and adequate lifestyle changes could be advised.